Multi-Species Feeding Association Dynamics Driven by a Large Generalist Predator - Gostischa, Julia; Massolo, Alessandro; Constantine, Rochelle (Frontiers in Marine Science, 2021)
Multi-species feeding associations (MSFAs) are temporary communities of animals exploiting the same or co-occurrent resources. Their dynamics are species dependent, often creating competitive interactions, but they can also increase foraging efficiency and ultimately individual fitness. The foraging behaviors of some species can enhance prey capture by others, with different roles depending on the species present. Here we use the Hauraki Gulf, New Zealand, as a model system to quantitatively characterize the principal types of MSFAs between 2011 and 2020. We determine the foraging associations of a large generalist predator, the Bryde’s whale, and how shifts in its prey preference changes the dynamics between seabird competitors. Hierarchical clustering from influential predator groups identified three types of MSFAs. Two of mainly fish-feeding predators, one including and one lacking Bryde’s whales, and one involving (although not limited to) plankton-feeders associated with Bryde’s whales. Cluster frequencies featured significant temporal trends, whereas MSFA diversity and whale association rate showed no significant changes. Bryde’s whales’ increasing reliance on zooplankton highlights their foraging plasticity, with changes in cluster frequencies and resource competition related to this shift from fish to zooplankton. The role of Bryde’s whales varies from joiners and terminators in fish-feeding aggregations to initiators with plankton-feeding seabird associations, thereby changing the MSFA dynamics. MSFAs tend towards a diversity equilibrium, i.e. a maximum number of species involved before competitive effects exceed the benefits of interaction. Functional MSFAs where heterospecific interactions are important to foraging success can be affected by changing composition. Future work should focus on the behavioural interactions between key predators, prey availability and their effect on MSFAs.